Lokakarya Pengembangan Teknologi Pendidikan bagi Guru-Guru di Desa Ujung Gunung Ilir - Serepina Hasibuan; Nova Ritonga; Desmon Adu; Setiaman Larosa; Daniel Daniel; Rudy Roberto Walean; Saedo Marbun (Sekolah Tinggi Teologi Real Batam, 2023)
The digital era certainly has implications for the use of technology in the world of education. The more developed the times, the more superior the resources. One of the standards of excellence of an educational institution is the sophisticated technology used. Therefore, technology needs to be mastered by educational actors. PkM activities are carried out by the tutoring method where teachers are directly guided in technology practice. Before carrying out PkM activities, the team conducted observations and interviews with several teachers and after the activities the team evaluated the results of the activities. PkM conducted by STTMSL lecturers and students aims to equip elementary, middle and high school teachers around the campus environment with adequate technological capabilities for this digital era. The activity carried out on November 15, 2022 was held with three sessions, namely: making creative and interactive PPT slides, making questions and assessment graphs from google forms and how to use them and introducing the Canva application as one of the applications that help teachers to prepare designs for certificates, diplomas, flyers, posters, advertisements, short videos for learning, and so on. Through this activity, teachers can improve their self-competence, especially in terms of utilizing technology to support learning in schools.Keywords: canva; digital; google forms; workshop; powerpoint; technology AbstrakEra digital tentunya berimplikasi pada penggunaan teknologi dalam dunia pendidikan. Semakin berkembangnya zaman maka semakin unggul pula sumber dayanya. Salah satu standar keunggulan suatu lembaga pendidikan adalah canggihnya teknologi yang digunakan. Oleh karena itu, teknologi perlu dikuasai oleh pelaku pendidikan. Kegiatan PkM dilakukan dengan metode tutoring di mana guru secara langsung dibimbing dalam praktik teknologi. Sebelum melaksanakan kegiatan PkM, Tim melakukan observasi dan wawancara dengan beberapa guru dan setelah kegiatan tim melakukan evaluasi hasil kegiatan. PkM yang dilakukan oleh dosen dan mahasiswa STTMSL bertujuan untuk memperlengkapi guru-guru SD, SMP dan SMA di sekitar lingkungan kampus dengan kemampuan teknologi yang memadai untuk era digital ini. Kegiatan yang dilakukan pada tanggal 15 November 2022 diselenggarakan dengan tiga sesi yakni: membuat slide PPT kreatif dan interaktif, membuat soal dan grafik penilaian dari google form dan bagaimana penggunaanya serta memperkenalkan aplikasi Canva sebagai salah satu aplikasi yang membantu guru untuk mempersiapkan desain sertifikat, ijazah, flyer, poster, iklan, video singkat untuk pembelajaran, dan lain sebagainya. Melalui kegiatan ini, guru-guru dapat meningkatkan kompetensi diri khususnya dalam hal memanfaatkan teknologi untuk mendukung pembelajaran di sekolah. Kata kunci: canva; digital; formulir google; lokakarya; powerpoint; teknologi